Ekspresi Seni Orang Miskin Sebagai Kebutuhan Integratif - Prof. Dr. Tjetjep Rohendi Rohidi MA (Jurnal Budaya Nusantara, 2015)
Human need to express the feeling of beauty seem to apply universally and last long time.